Phân tích thành nhân tử
( a - x ) . y3 - ( a - y ) . x3 + ( x - y ) . a3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: (x+y+z)^3-x^3-y^3-z^3
=(x+y+z-x)(x^2+2xy+y^2-x^2-xy-xz+z^2)-(y+z)(y^2-yz+z^2)
=(x+y)(y+z)(x+z)
b: x^3+y^3+z^3=1
x+y+z=1
=>x+y=1-z
x^3+y^3+z^3=1
=>(x+y)^3+z^3-3xy(x+y)=1
=>(1-z)^3+z^3-3xy(1-z)=1
=>1-3z-3z^2-z^3+z^3-3xy(1-z)=1
=>1-3z+3z^2-3xy(1-z)=1
=>-3z+3z^2-3xy(1-z)=0
=>-3z(1-z)-3xy(1-z)=0
=>(z-1)(z+xy)=0
=>z=1 và xy=0
=>z=1 và x=0; y=0
A=1+0+0=1
x 3 – x + y 3 – y
= ( x 3 + y 3 ) − (x + y)
= (x + y)( x 2 – xy + y 2 ) − (x + y)
= (x + y)( x 2 – xy + y 2 − 1)
= (√x - √y)(√x + √y)2
= (√x - √y)(√x + √y)(√x + √y)
= (x - y)(√x + √y)
x 3 - x + 3 x 2 y + 3 x y 2 + y 3 - y = x 3 + 3 x 2 y + 3 x y 2 + y 3 - x - y = x + y 3 - x - y = x + y x + y 2 - 1 = x + y x + y + 1 x + y - 1
a) 12x. b) 4xy
c) 2y(3 x 2 + y 2 ).
d) (x + y + z)( x 2 + y 2 + z 2 – xy – xz - yz).
a) ab + b√a + √a + 1 = [(√a)2b + b√a] + (√a + 1)
= b√a(√a + 1) + (√a + 1) = (√a + 1)(b√a + 1)
= (√x - √y)(√x + √y)2
= (√x - √y)(√x + √y)(√x + √y)
= (x - y)(√x + √y)
Bài 2:
a: \(x^2+5x-6=\left(x+6\right)\left(x-1\right)\)
b: \(5x^2+5xy-x-y\)
\(=5x\left(x+y\right)-\left(x+y\right)\)
\(=\left(x+y\right)\left(5x-1\right)\)
c:\(-6x^2+7x-2\)
\(=-6x^2+3x+4x-2\)
\(=-3x\left(2x-1\right)+2\left(2x-1\right)\)
\(=\left(2x-1\right)\left(-3x+2\right)\)
1.
a) \(=x^2\left(x^2+2x+1\right)=x^2\left(x+1\right)^2\)
b) \(=\left(x+y\right)^3-\left(x+y\right)=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\)
\(=\left(x+y\right)\left(x+y-1\right)\left(x+y+1\right)\)
c) \(=5\left[\left(x^2-2xy+y^2\right)-4z^2\right]=5\left[\left(x-y\right)^2-4z^2\right]\)
\(=5\left(x-y-2z\right)\left(x-y+2z\right)\)
2.
a) \(=x\left(x+2\right)+3\left(x+2\right)=\left(x+2\right)\left(x+3\right)\)
b) \(=5x\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(5x-1\right)\)
c) \(=-\left[3x\left(2x-1\right)-2\left(2x-1\right)\right]=-\left(2x-1\right)\left(3x-2\right)\)
3.
b) \(=2x\left(x-1\right)+5\left(x-1\right)=\left(x-1\right)\left(2x+5\right)\)
c) \(=-\left[5x\left(x-3\right)-1\left(x-3\right)\right]=-\left(x-3\right)\left(5x-1\right)\)
4.
a) \(\Rightarrow\left(x-1\right)\left(5x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{1}{5}\end{matrix}\right.\)
b) \(\Rightarrow2\left(x+5\right)-x\left(x+5\right)=0\)
\(\Rightarrow\left(x+5\right)\left(2-x\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)
\(=\left(x+y\right)^3-\left(x+y\right)=\left(x+y\right)\left(x^2+2xy+y^2-1\right)\)
\(x^3-x+3x^2+3xy^2+y^3-y\)
\(=\left(x+y\right)^3-\left(x+y\right)\)
\(=\left(x+y\right)\left(x+y+1\right)\left(x+y-1\right)\)
\(\left(x+y-z\right)^3-x^3-y^3+z^3\)
\(=\left[\left(x+y\right)-z\right]^3-x^3-y^3+z^3\)
\(=\left(x+y\right)^3-z^3-3\left(x+y\right)z\left(x+y-z\right)-x^3-y^3+z^3\)
\(=x^3+y^3-z^3+3xy\left(x+y\right)-3\left(x+y\right)z\left(x+y-z\right)-x^3-y^3+z^3\)
\(=3xy\left(x+y\right)-3z\left(x+y\right)\left(x+y-z\right)\)
\(=3\left(x+y\right)\left[xy-z\left(x+y-z\right)\right]\)
\(=3\left(x+y\right)\left(xy-zx-yz+z^2\right)\)
\(=3\left(x+y\right)\left[x\left(y-z\right)-z\left(y-z\right)\right]\)
\(=3\left(x+y\right)\left(y-z\right)\left(x-z\right)\)
#\(Urushi\text{☕}\)
Áp dụng (a+b)3 = a3+b3+3ab(a+b), ta có:
(x+y+z)3-x3-y3-z3
=[(x+y)+z]3-x3-y3-z3
=(x+y)3+z3+3z(x+y)(x+y+z)-x3-y3-z3
=x3+y3+3xy(x+y)+z3+3z(x+y)(x+y+z)-x3-y3-z3
=3(x+y)(xy+xz+yz+z2)
=3(x+y)[x(y+z)+z(y+z)]
=3(x+y)(y+z)(x+z)